Pathways for the Reactions Between Neurotoxic Organophosphorus Compounds and Oximes or Hydroxamic Acids. Issue 35 (21st November 2016) - Bierwisch, Anne; Koller, Marianne; Worek, Franz; Kubik, Stefan
Abstract : To obtain mechanistic insight into the recently demonstrated detoxification ability of β‐cyclodextrin derivatives containing substituents with oxime or hydroxamic acid residues, analogous glucose derivatives with the same substituents were treated with cyclosarin (GF), tabun (GA), and O ‐ethyl S‐[2‐(diisopropylamino)ethyl] methylphosphonothioate (VX) in (Tris)‐HCl buffer (0.1m, pH 7.40), and the different reaction pathways were studied by 31 P NMR spectroscopy and mass spectrometry. Consistent with previous reports, the oxime is phosphonylated by GF, which is followed by elimination of O ‐cyclohexyl methylphosphonate to afford a nitrile. Reaction of the hydroxamic acid with GA depends on whether the nitrogen atom of the hydroxamic acid bears a substituent or not. The unsubstituted hydroxamic acid affords a stable phosphate ester lacking the cyanide and the dimethylamino group of GA. If the hydroxamic acid is methylated, the initially formed phosphorylated product undergoes a number of transformations, including cleavage of the C–N bond of the hydroxamic acid. Reaction of the hydroxamic acid with VX involves a Lossen rearrangement. These investigations thus show that all investigated nucleophiles are irreversibly modified upon reaction with nerve agents under the chosen conditions, which indicates that cyclodextrins with oximes or hydroxamic acid as substituents are unlikely to afford catalytic nerve‐agent scavengers. Abstract : The reactions between oximes and hydroxamic acids and nerve agents such as cyclosarin, tabun, and VX in Tris‐HCl buffer at pH 7.40 involve initial phosphonylation or phosphorylation at the oxygen atom followed by another transformation that depends on the α‐effect nucleophile and the nerve agent but that consistently leads to irreversible modification of the nucleophilic functional group.